Making a film to share traditional engineering techniques to tackle the global water crisis. Issue 4 (18th June 2021) - Bingham, Louise; Hetherington, David
Abstract : Civil engineers in the UK have teamed up with a water charity to make an educational film that helps communities in semi-arid climates manage their water. The team learnt how to construct simple dams, known in India as 'johads', that harvest seasonal rainfall, reducing flood and drought risk. They then built a new dam and restored another in Rajasthan district, recording the process to enable others to replicate the work. A language-neutral educational film was then produced and tested with other communities in India and Colombia to ensure applicability to a variety of geographies, cultures and environments. Educating communities on water management in this way will help to achieve the United Nations sustainable development goal 6: clean water and sanitation for all.